SOUTH KOREAâ€™S STRATEGY IN IMPROVING HALAL TOURISM FOR INTERESTING MUSLIM TOURIST - Safitri, Ledya; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research aims to discuss the strategic aspects of South Korea in improving halal tourism. At present, halal tourism has become popular. The development of halal tourism began to be carried out by several countries, Muslim and non-Muslim countries. South Korea seeks to develop the halal tourism sector to interest Muslim tourist visits to the country. To take advantage of these opportunity, South Korea promotes â€œMuslim Friendly Koreaâ€ slogan.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Theory used in the research is soft diplomacy of Joseph Nye. The method used in this research is descriptive qualitative. The data were collected through analysis. The technique of data analysis which used in this research was qualitative method and descriptive approachment. This research will explore the development of halal tourism in several countries, reviewing the concepts and principles of halal tourism, and discuss the chances and challenges.Â This research shows that South Korea makes effort to develop halal tourism inÂ interest Muslim tourists through the concept Muslim Friendly Tourism. Improving the facilities and services based on concept of Muslim friendly. Also South Korea determines the halal certification, standard operational and halal requirements.Keywords: halal tourism, Muslim tourist, Muslim Friendly Korea, Muslim Friendly Tourism.